Posterior uniportal video-assisted thoracoscopic surgery for anatomical lung resections - BOSTANCI, KORKUT (AME PUBL CO, 2017)
Background: The acceptance of uniportal video-assisted thoracoscopic surgery (uVATS) for anatomical lung resections has been growing in recent years. This study presents the first case-series in the literature with posterior uVATS (puVATS) technique for specific anatomical lung resections. Methods: The first 20 consecutive patients who underwent an anatomical lung resection by a single surgeon, by means of puVATS technique were evaluated in terms of pre-, peri- and post-operative results. A single incision of 3.5-4.5 cm was made posteriorly in the 6th intercostal space at the so-called 'triangle of auscultation' to perform a resection of either a posterior segment of an upper lobe or a superior segment of a lower lobe for both lungs. Results: There were 5 posterior segmentectomies and 3 apical segmentectomies of the right upper lobe and 6 apical segmentectomies of the left lower lobe. Moreover, there were 6 lobectomies, all except for one as an extension of initially planned posterior segmentectomy. There were no intraoperative complications. Median tumor size (IQR) was 1.65 cm (1.1-2.57 cm), while median incision size (IQR) was 3.5 cm (3.5-3.87 cm). Median operative time (IQR) was 160 minutes (142-178 minutes). Median number of removed lymph nodes (IQR) was 19 [15-20]. Four patients had postoperative complications: three had bronchitis and one developed heart failure, all of which resolved before patients were discharged. Median length of hospital stay (IQR) was 6 days (5-8 days). Conclusions: puVATS approach for posterior lung segment resections, even for lobectomy if needed, seems to be feasible and safe. Exposure of the bronchovascular structures of the 'posterior segments' is better, and local and mediastinal lymphadenectomy seem to be easier with access directly in front of the incision and the lung, rather than behind it.
Keywords: Uniportal video-assisted thoracoscopic surgery (uVATS); posterior approach; anatomical lung resection; LOBECTOMY; CANCER